Not just code: a framework for community governance and management in Decentralized Autonomous Organizations - Viaro Bridi, Thomaz Henrique; Andrlić, Berislav; Gonçalves, Rodrigo Franco (Frontiers in Blockchain, 2025)
The concept of Decentralized Autonomous Organizations (DAOs) has introduced a novel paradigm in organizational governance, characterized by more collaborative decision-making. However, the lack of established organizational frameworks for DAOs presents significant challenges to their constitution, stability, and longevity. Aiming to address this shortcoming, this paper presents a conceptual framework to guide the design of the community governance structure of DAOs. To achieve this aim, we employed two complementary methods: firstly, we conducted a systematic literature review about DAOs and community governance; secondly, we conducted an analysis of the governance methods employed by five DAOs operating in public blockchain ecosystems. The proposed framework provides a valuable tool for DAO founders, developers, and community members to design and implement effective governance structures and contributes to the understanding of DAO governance and further research.